The incidence of Aeromonas hydrophila in Nile Tilapia (Oreochromis niloticus) from the West Bay of Laguna de Bay, Barangay Bayanan, Muntinlupa City - Rodriguez, Katarina (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2006)
Aeromonas hydrophila is a gram negative bacillus that has been associated with fish and zoonotic diseases. Its incidence in Oreochromis niloticus (Nile Tilapia) sampled in June, September and November 2005 from the West Bay of Laguna de Bay was found to be 3%. The isolates were from the gastrointestinal tracts of the fish. The low incidence maybe associated with the environmental factors that showed good water quality such as low nitrate level, high dissolved oxygen level and low temperature in the bay. Test for virulence showed that the A. hydrophila isolates were not able to produce diseases in tilapia in the laboratory, suggesting that these were avirulent strains. However, the microorganisms were still recovered 7 d after their inoculation on the skin of the fish, showing their persistence in the animal hosts.